Ore mineralization of the Mutnovskoe gold-silver-base metal deposit, nothern flank (Kamchatka) - P.E. Schweigert; P.S. Zhegunov; S.V. Moskaleva (Вестник Камчатской региональной ассоциации "Учебно-научный центр". Серия: Науки о Земле, 2024)
The Mutnovskoe deposit is located in the south of the Central Kamchatka volcanic belt (Kamchatka peninsula, Russia). Ore bodies are concentrated within the N-S oriented «Opredelyayushchaya» vein zone, which is located in the central part of the cognominal to the deposit ore field. The vein zone is subdivided by ore mineralization type distribution to northern, southern and central parts, traditionally called flanks. Two stages of ore formation are distinguished: gold-silver mostly distributed in the north flank, and silver-base metal in the southern and central flanks. This work shows the results of mineralogical study of drill core samples taken from drill wells in the northern flank. Typomorphic features of the main ore minerals are compared with the results of the previous mineralogical studies of southern flank. Such minerals as hessite, proustite-pyrargyrite and pearceite-polybasite are described in the ores of the northern flank for the first time. Native gold purity differentiation may indicate the presence of hidden mineralogical zonality of products of the gold-silver stage of ore formation.